The Oncogenic Roles of JC Virus T Antigen in Breast Carcinogenesis - Zheng, Hua-chuan; E, Ying; Cui, Zheng-guo; Zhao, Shuang; Zhang, Yong (Frontiers in Molecular Biosciences, 2021)
Purpose: JC virus (JCV) infects 80-90% of the population, and results in progressive multifocal leukoencephalopathy upon immunodeficiency. The study aimed to pathologically clarify the oncogenic roles of T antigen in human breast cancers. Methods: Breast cancers, dysplasia and normal tissues were examined for T antigen of JCV by nested and real-time PCR. The positive rate or copy of T antigen was compared with clinicopathological parameters of breast cancer. JCV existence was morphologically detected by immunohistochemistry and in situ PCR. T antigen was examined by Western blot using frozen samples of breast cancer and paired normal tissues. Results: According to nested PCR, the positive rate of breast ductal or lobular carcinoma was lower than normal tissue (p<0.05). T antigen existence was negatively correlated with E-cadherin expression and triple-negative breast cancer (p<0.05), but positively with lymph node metastasis, estrogen receptor and progestogen receptor expression (p<0.05). Quantitative PCR showed that JCV copies were gradually decreased from normal tissue, dysplasia to cancer (p<0.05). JCV T antigen copy was lower in ductal adenocarcinoma than normal tissue (p<0.05), in line with situ PCR and immunohistochemistry. JCV copies were negatively correlated with tumor size and E-cadherin expression (p<0.05), but positively with G grading of breast cancer (p<0.05). Western blot also indicated weaker T antigen expression in breast cancer than normal tissues (p<0.05). Conclusions: JCV T antigen might play an important role in breast carcinogenesis. It can be employed as a molecular marker for the differentiation and aggressive behaviors of breast cancer.